2017
DOI: 10.1209/0295-5075/120/40002
|View full text |Cite
|
Sign up to set email alerts
|

Perfect synchronization in networks of phase-frustrated oscillators

Abstract: Synchronizing phase frustrated Kuramoto oscillators, a challenge that has found applications from neuronal networks to the power grid, is an eluding problem, as even small phase-lags cause the oscillators to avoid synchronization. Here we show, constructively, how to strategically select the optimal frequency set, capturing the natural frequencies of all oscillators, for a given network and phase-lags, that will ensure perfect synchronization. We find that high levels of synchronization are sustained in the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…is the DC bias current. It is to be mentioned that the isolated RSCJ model has similarities with the Sakaguchi-Kuramoto phase model with inertia [43][44][45] and also with the working model of a power grid [46]. In the absence of coupling ( = 0) and a = 1.5, each node can reveal two types of dynamics: oscillatory spiking behavior (I i > 1.0) and a quiescent state (I i < 1.0).…”
Section: Prediction Of Bursting and Clustering: Network Of Josepmentioning
confidence: 99%
“…is the DC bias current. It is to be mentioned that the isolated RSCJ model has similarities with the Sakaguchi-Kuramoto phase model with inertia [43][44][45] and also with the working model of a power grid [46]. In the absence of coupling ( = 0) and a = 1.5, each node can reveal two types of dynamics: oscillatory spiking behavior (I i > 1.0) and a quiescent state (I i < 1.0).…”
Section: Prediction Of Bursting and Clustering: Network Of Josepmentioning
confidence: 99%
“…In particular, the Kuramoto model as a paradigm for general oscillator models has been intensively investigated recently [7], from the perspective of networked control [10], selforganized synchronization [12][13][14][15][16][17], to stability against even large perturbations [18,19]. e further investigation of the Kuramoto model with or without inertia attracts great interest from the aspects of, e.g., the optimal placement of virtual inertia for system performance [20] and for perfect synchronization [21,22], non-Gaussian frequency fluctuations described by Levy-stable laws [23]. From the viewpoint of power grid operators, it is vital yet challenging to enhance network stability in complex power grids, especially in the presence of electricity markets [4].…”
Section: Introductionmentioning
confidence: 99%
“…In [33], it was observed that lags alone may be used to control the system to a predefined frequency for the complete network case. In [34], a similar mechanism was used for sparser graphs to enable frequencies to be selected in order to provide for perfect synchronisation. In our previous paper [35] we showed how a form of codynamics, namely adaptive lags, where the λ i become functions of time with their own evolution equation, can improve synchronisation for sparse networks -indeed, achieve perfect phase synchronisation.…”
Section: Introductionmentioning
confidence: 99%